Un manufatto ambiguo. Le contrastate vicende e i contradditori significati di un moderno mulino elettrico - Sansa, Renato (OS. Opificio della Storia, 2023)
Istria was, for many aspects, a poor region after the annexation to Italy. The exclusion to wider commercial circuits, whose was part as a region of the Austro-Hungarian Empire, worsened the agriculture. The prices of agriculture products lowered. Despite all this, some entrepeneurs were able to launch new initiatives, as the establishment of a company, the Societ. Istriana di Macinazione, in order to build up the first Istrian electric mill with a modern silo in the port of Pula. The timing of the operation, the mill was completed in 1941, was critical, and some problems arose after the end of the war.